Spatially branched CdS-Bi2S3 heteroarchitecture: single step hydrothermal synthesis approach with enhanced field emission performance and highly responsive broadband photodetection - Bankar, Prashant K.; Pawar, Mahendra S.; Pawbake, Amit S.; Warule, Sambhaji S.; Late, Dattatray J.; More, Mahendra A. (RSC Advances, 2016)
This report explores the controlled hierarchical synthesis of CdS nanostructure branches on Bi2S3 nanorod cores via a facile single step hydrothermal route. Morphological and structural studies reveal the formation of CdS-Bi2S3 heteroarchitecture with excellent stoichiometry between the constituent elements. The growth of CdS over Bi2S3 strongly depends on optimization of the reaction conditions, especially low PVP concentration. Furthermore, the as-synthesized CdS-Bi2S3 heteroarchitecture demonstrates multifunctionality in field emission and photoresponse. Interestingly, the CdS-Bi2S3 heteroarchitecture shows enhanced field emission properties such as low turn-on field (similar to 1.8 V mu m(-1) for 10 mu A cm(2)), high emission current density and better current stability in comparison to Bi2S3 and other nanostructures. The as-synthesized CdS-Bi2S3 heteroarchitecture exhibits considerable response and recovery times, similar to 207 ms and 315 ms, respectively in comparison to bare Bi2S3 nanostructures (similar to 655 ms and 678 ms). The present results demonstrate CdS-Bi2S3 heteroarchitecture as a potential candidate for future optoelectronic device applications.

Synthesis of orthorhombic-molybdenum trioxide (α-MoO3) thin films by hot wire-CVD and investigations of its humidity sensing properties - Jadkar, Vijaya; Pawbake, Amit S.; Waykar,Ravindra G.; Jadhavar, Ashok Arjun; Mayabadi, Azam; Date, Abhijit; Late, Dattatray J.; Pathan, Habib M.; Gosavi, Suresh W.; Jadkar, Sandesh R. (Journal of Materials Science Materials in Electronics, 2017)
In present work, we report synthesis of orthorhombic-molybdenum trioxide (α-MoO 3) thin films using home-build hot wire-CVD (HW-CVD) method simply by heating the Mo filament in a controlled O 2 atmosphere. The formation of α-MoO 3 was confirmed by low angle-XRD and Raman spectroscopy. Low angle-XRD analysis revealed that α-MoO 3 crystallites have orientations along (110), (101) and (111) directions while Raman spectroscopy analysis shows two prominent vibrational modes ~819 and ~994 cm −1 associated with Mo 2–O and Mo=O respectively. SEM and TEM analysis show the formation of nano-sheets like morphology of α-MoO 3 thin films. The SAED pattern shows highly crystalline nature of α-MoO 3. The humidity-sensing properties were investigated at room temperature by fabricating the two probe device. The humidity sensing results showed n-type behavior of α-MoO 3. The maximum humidity sensitivity of ~6957% along with response time of ~66 s and recovery time of ~5 s were observed for α-MoO 3 thin film humidity sensor device. Our results have opened up a new avenue to grow α-MoO 3 for humidity sensor applications.

Superior humidity sensor and photodetector of mesoporous ZnO nanosheets at room temperature - Gupta, Shobhnath P.; Pawbake, Amit S.; Sathe, Bhaskar R.; Late, Dattatray J.; Walke, Pravin S. (Sensors and Actuators B-Chemical, 2019)
Miniaturized sensor technology is vastly demanding multifunctional materials to fulfill many requirements simultaneously; instead of integrating various sensors into a single device. Efficient operation of these miniaturized sensors at room temperature is highly feasible and cost-effective. The humidity sensing and photodetection is precise merit of sensing in special usage like artificial skin. Sensitivity enhancement in both humidity and photodetection required the high surface area for adsorption as well as a high charge transfer mechanism. The two dimensional (2D) zinc oxide nanosheets (ZnO NS) is the ultimate structure for dimensionally confined transport properties owing to the specific surface atomic configuration that results in high sensitivity, low operating temperature, fast response and recovery, and improved selectivity. Furthermore, introducing porosity into 2D nanostructures has opened new opportunities to enhance the efficiency of sensors and detectors via increasing large surface area and tunable physical and chemical properties. Here we report preparation of mesoporous and highly crystalline 2D ZnO NS by a single step, template free, cost-effective chemical method. The structural and morphological characterizations of ZnO NS are carried out using XRD, FESEM, XPS, TEM respectively. The high-resolution TEM images emphasize sheet-like morphology with a thickness of around 18-22 nm. Further the mesoporous ZnO NS (MZNS) with the pore size between 5-10 nm are achieved by simple heat-treatment. XPS and PL study is confirming the oxygen deficiency in MZNS. The MZNS exhibits an excellent responsivity than PZNS with a fast response and rapid recovery time of 25 s and 5 s respectively along with good cyclic stability which is highly crucial for smart humidity sensor. Furthermore, it considerably enhances photo-sensor performance than pristine ZnO NS (PZNS) with (similar to)1 s response time as well as (similar to)1 s recovery time along with better stability. These promising results illustrate the great potential of MZNS for next-generation humidity sensors and photodetectors.
Keywords: humidity sensor; Mesoporous; nanosheets; Photo-detector